Replacement of a protein-energy supplement by a same-cost maize-based supplement on performance and product quality of pasture-finished Nellore heifers - Souza Castro, Laura Cristina; Campos, Wellington da Costa de; Oliveira, Ivanna Moraes de [UNESP]; Fernandes, Rodolfo Maciel [UNESP]; Moretti, Matheus Henrique; Piza Roth, Marcella Toledo; Resende, Flavio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP] (Csiro Publishing, 2020)
Context In the largest beef-producing countries in the world, the slaughter of female cows accounts for similar to 30-40% of all beef produced. Aims The objective of this study was to evaluate the replacement of a protein-energy supplement (PES) by a same-cost maize-based supplement (MBS) on the performance and final product of Nellore heifers grazingBrachiaria brizanthacv. Marandu pasture during the wet season in Brazil. Methods Ninety-six Nellore heifers of bodyweight (BW) 281 +/- 7.55 kg and aged 23 months were used. Six were slaughtered at the start of the experiment. The remaining 90 heifers received one of the following three supplements with their predominantly pasture diet for 133 days: control, mineral saltad libitum; PES, with protein 250 g/kg dry matter (DM) and total digestible nutrient 600 g/kg DM, offered at 3 g/kg BW.day (as-fed basis); MBS, with crude protein 90 g/kg DM and total digestible nutrient 850 g/kg DM, offered at 7 g/kg BW.day (as-fed basis). The variables were evaluated in a completely randomised block design with 30 heifers per treatment. Key results Average daily gain and final BW were similar (P> 0.05) in PES and MBS treatments, and relative to the control increased (P< 0.01) average daily gain by similar to 24% and final BW by 7%. Pasture intakes were decreased, with substitution levels of 8.0% for heifers receiving PES and 10.4% for those receiving MBS. Carcass weight (kg/day) and carcass gain (g carcass/kg BW) were greater (P< 0.001) for heifers receiving MBS and PES than for the control group. Backfat depth was greater (P< 0.001) in heifers receiving MBS (7.91 mm) than in those receiving PES (6.25 mm), and the lowest (P< 0.001) measurement was observed in the control group (4.85 mm). Conclusions Maize-based supplement (7 g/kg BW.day) provided the same growth rate as PES (3 g/kg BW.day) but yielded heavier and slightly fatter carcasses of pasture-finished Nellore heifers during the wet season (133 days) with a similar cost, and with more total digestible nutrients than pasture plus mineral salt. Implications Maize-based supplement provided to Nellore heifers on pasture may improve performance despite lower pasture intakes but needs to be evaluated carefully in terms of costs involved.
Keywords: body composition; rates of gain